COMPARATIVE THERAPEUTIC RESPONSE TO PEGYLATED INTERFERON PLUS RIBAVIRIN VERSUS INTERFERON ALPHA-2b IN CHRONIC HEPATITIS C PATIENTS - Ali, Shafqut; Nazir, Ghazala; Khan, Shahbaz Ali; Iram, Samia; Fatima, Fozia (Journal of Ayub Medical College Abbottabad, 2010)
Background: Hepatitis C is an epidemic worldwide since discovery in 1989. Conventional interferon alpha-2b plus Ribavirin therapy was started in 1998 but over all sustained viral response (SVR) rates are much below the desired rates to eradicate the diseases and stopping its epidemic. This study was conducted to access the therapeutic and cost-effectiveness of long acting pegylated interferon alpha-2b plus Ribavirin therapy verses conventional interferon alpha-2b plus Ribavirin. Methods: This comparative study was done at PAF Hospital Shorkot Cantt from July 2005 to July 2008. One hundred anti-HCV positive patients were selected randomly for the study according to willingness due to cost affordability of the patients for conventional interferon. Group-A was labelled as pegylated interferon alpha-2b plus Ribavirin group, and Group-B interferon alpha-2b plus Ribavirin group. Both groups were given treatment for 24 weeks. Early virological response (EVR) was accessed at 12 weeks of treatment. Sustained virological response (SVR) in both the groups was done at 24th week during the treatment and 6 monthly after treatment for 2 years. Initially non-responders and relapsed patients within 2 years of treatment were re-treated for 24 weeks with the same treatment. In both groups nonresponders and relapsed patients were labelled as resistant patients. Both groups were followed with same protocol for 2 years. Results: Out of 100 patients included in the study, 34% were females and 66% were males. Group-A patients over all showed 94% SVR as compare to 80% in Group-B in 2 year follow-up. Group-A showed 6% resistant patients as compare to Group-B (20%). Conventional interferons were better tolerated. Higher incidence of side-effects was seen in Group-A. Conclusion: Pegylated interferon plus Ribavirin showed 94% SVR in 2 years. Pegylated interferon plus Ribavirin is the treatment of choice. Keywords: Anti-HCV, ELISA, PCR, SVR, Pegylated-interferon, Interferon Alpha-2b, Ribavirin